2021
DOI: 10.1080/12298093.2021.1937882
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis and Expression Profiling of Molecular Responses to Cd Toxicity in Morchella spongiola

Abstract: Morchella is a genus of fungi with the ability to concentrate Cd both in the fruit-body and mycelium. However, the molecular mechanisms conferring resistance to Cd stress in Morchella are unknown. Here, RNA-based transcriptomic sequencing was used to identify the genes and pathways involved in Cd tolerance in Morchella spongiola. 7444 differentially expressed genes (DEGs) were identified by cultivating M. spongiola in media containing 0.15, 0.90, or 1.50 mg/L Cd 2þ . The DEGs were divided into six sub-clusters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Therefore, acidophilic iron–sulfur-oxidizing microorganisms can oxidize Fe 2+ and sulfur in the environment through oxidative phosphorylation and synthesize ATP in cells (Quatrini et al 2009 ; Bathe and Norris 2007 ). The transcriptome of Morchella spongiola under Cd 2+ stress was analyzed with results showing that the oxidative phosphorylation pathway was very beneficial to the detoxification mechanism of Cd 2+ (Xu et al 2021 ). Researchers found that under the stress of Cu 2+ , the mRNA expression of F-type ATPase involved in oxidative phosphorylation pathway in A. caldus are significantly up-regulated, and the mRNA expression of NADH dehydrogenase is significantly down-regulated.…”
Section: Transcriptome Analysis In Bioleaching Under the Metal Ion Tressmentioning
confidence: 99%
“…Therefore, acidophilic iron–sulfur-oxidizing microorganisms can oxidize Fe 2+ and sulfur in the environment through oxidative phosphorylation and synthesize ATP in cells (Quatrini et al 2009 ; Bathe and Norris 2007 ). The transcriptome of Morchella spongiola under Cd 2+ stress was analyzed with results showing that the oxidative phosphorylation pathway was very beneficial to the detoxification mechanism of Cd 2+ (Xu et al 2021 ). Researchers found that under the stress of Cu 2+ , the mRNA expression of F-type ATPase involved in oxidative phosphorylation pathway in A. caldus are significantly up-regulated, and the mRNA expression of NADH dehydrogenase is significantly down-regulated.…”
Section: Transcriptome Analysis In Bioleaching Under the Metal Ion Tressmentioning
confidence: 99%
“…Multiomics studies related to Morchella have been a prominent trend in recent years. The research subjects have mainly focused on the growth and development of M. importuna and M. sextelata , including the comparative transcriptome, metabolome, secretome, and proteome at the stage of the growth and development of mycelia, sclerotia, and ascomata [ 32 , 36 , 40 , 62 , 63 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ]. However, these studies have mostly concentrated at the upper level, and the exploration of functional genes, regulatory networks, or metabolic pathways that respond to development needs to be deepened.…”
Section: Relevance On Biological Research For Steady Cultivation Indu...mentioning
confidence: 99%
“…Yu, et al [128] used transcriptomic analysis to investigate two genotypes of Lentinula edodes with differing Cd accumulation capacities and found that the high Cd accumulation type Le4625 had approximately three times more Cd than the low Cd accumulation type Le4606. Additionally, transcriptome and expression profiling of the molecular response of M. spongiola in Cd toxicity revealed the major detoxification pathways under Cd stress, including MAPK signaling, oxidative phosphorylation, pyruvate metabolism, and propanoate metabolism, offering a new pathway and possibility for bioremediation in Cd stress [143]. Breeding low HM accumulation varieties is a key research direction, with common mushroom breeding methods, including cross-breeding, radiation and chemical mutagenesis breeding, and transgenic breeding.…”
Section: Screening and Cultivation Of Suitable Strainsmentioning
confidence: 99%